2015
DOI: 10.1073/pnas.1505289112
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein S6 kinase 1 signaling in prefrontal cortex controls depressive behavior

Abstract: Current treatments for major depressive disorder (MDD) have a time lag and are ineffective for a large number of patients. Development of novel pharmacological therapies requires a comprehensive understanding of the molecular events that contribute to MDD pathophysiology. Recent evidence points toward aberrant activity of synaptic proteins as a critical contributing factor. In the present studies, we used viral-mediated gene transfer to target a key mediator of activity-dependent synaptic protein synthesis dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 25 publications
7
46
1
Order By: Relevance
“…Each bar represents the mean±SD of three independent experiments; *p<0.001, compared with control, one-way ANOVA or Student-Newman-Keuls Phosphorylation activation of downstream substrates is the major activation of mTORC1 signaling pathway. Ribosomal protein S6 kinase 1 (S6K1) is a key substrate for the activation of the phosphorylation levels of mTORC1 signaling pathway [13]. In order to investigate whether mTORC 1 pathway is involved in the regulation of autophagy in HeLa cells induced by quercetin, Western blot was used to detect the phosphorylated protein expression levels of S6K1 (p-S6K1) and S6KI in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Each bar represents the mean±SD of three independent experiments; *p<0.001, compared with control, one-way ANOVA or Student-Newman-Keuls Phosphorylation activation of downstream substrates is the major activation of mTORC1 signaling pathway. Ribosomal protein S6 kinase 1 (S6K1) is a key substrate for the activation of the phosphorylation levels of mTORC1 signaling pathway [13]. In order to investigate whether mTORC 1 pathway is involved in the regulation of autophagy in HeLa cells induced by quercetin, Western blot was used to detect the phosphorylated protein expression levels of S6K1 (p-S6K1) and S6KI in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…For dendritic morphology, 0.4 million cells per 6-well were plated on coverslips. On DIV 3, cells were incubated with an AAV2 viral vector that expresses green fluorescence protein (AAV2-GFP) as previously described (Dwyer et al, 2015) for 72 hr. Following viral incubation, media was changed and cells were treated with ketamine (500 nM), LY 341495 (10 nM), or GLYX-13 (3nM) at DIV 17 and then fixed 24hr after with 4% PFA.…”
Section: Methodsmentioning
confidence: 99%
“…Ketamine administration rapidly increases phosphorylation of mTORC1 signaling proteins in the PFC and the behavioral effects of ketamine are blocked by pretreatment of the selective mTORC1 inhibitor rapamycin, providing further support for the role of mTORC1 in the rapid-acting antidepressant effects of ketamine [9, 55] (Figure 1). In addition, a recent study has demonstrated that expression of signaling proteins that increase or decrease mTORC1 signaling in the medial PFC produce antidepressant or pro-depressive actions, respectively [29, 56]. …”
Section: Mechanisms Underlying Rapid-acting Antidepressantsmentioning
confidence: 99%